2016
DOI: 10.1007/s00259-016-3320-x
|View full text |Cite
|
Sign up to set email alerts
|

18F-fluoromisonidazole positron emission tomography can predict pathological necrosis of brain tumors

Abstract: 2 AbstractPurpose:Tumour necrosis is one of the indicators of tumour aggressiveness.18 F-fluoromisonidazole (FMISO) is the most widely used positron emission tomography (PET) tracer to evaluate severe hypoxia in vivo. Because severe hypoxia causes necrosis, we hypothesized that intratumoural necrosis can be detected by FMISO PET in brain tumours regardless of their histopathology. We applied FMISO PET to various types of brain tumours before tumour resection and evaluated the correlation between histopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…We also observed a strong relationship between the presence of necrosis and 18 F-FMISO uptake, regardless of the pathological subtype [22]. However, other studies have reported that 18 F-FMISO uptake was observed in not only GBMs but also lower-grade gliomas [12,17,23].…”
Section: Glioblastoma (Gbm) Which Is Classified Among Gliomas As World Healthsupporting
confidence: 65%
“…We also observed a strong relationship between the presence of necrosis and 18 F-FMISO uptake, regardless of the pathological subtype [22]. However, other studies have reported that 18 F-FMISO uptake was observed in not only GBMs but also lower-grade gliomas [12,17,23].…”
Section: Glioblastoma (Gbm) Which Is Classified Among Gliomas As World Healthsupporting
confidence: 65%
“… 62 In the case of glioblastoma, high 18 F-FMISO uptake has been shown as a predictor of micronecrosis in humans. 63 …”
Section: Spatial Measurements Of Oxygenationmentioning
confidence: 99%
“…Several research groups have compared FMISO uptake with histological findings (such as necrosis and vascularization) and functional features (such as permeability). Our group investigated 59 patients with brain tumors including astrocytic tumors and metastatic tumors, and we examined the presence of microscopic necrosis [50]. In the visual analysis, 26 of the 27 FMISO-positive patients presented with necrosis, whereas 28 of the 32 FMISO-negative patients showed no necrosis.…”
Section: The Clinical Usefulness Of Fmisomentioning
confidence: 99%